Evaluation of Shear Bond Strength and Antimicrobial Effects of Resin-Modified Glass Ionomer Containing Titanium Oxide and Silver Nanoparticles - Davari, Abdolrahim; Mosaddegh, Ahmad; Daneshkazemi, Alireza; Frahat, Farnaz; Hakimzadeh, Alireza; Abbasi, Sepideh (Journal of Dental School, 2023)
Objectives Streptococcus mutans, as one of the most important cariogenic bacteria, is responsible for dental caries. To prevent and control dental caries, it is reasonable to use new materials and techniques for eradicating cariogenic bacteria. The present study aimed to evaluate and compare the antimicrobial effects of resin-modified glass ionomer (RMGI) containing silver and titanium oxide nanoparticles, on Streptococcus mutans (S. mutans) and to assess and compare the shear bond strength between coronal and radicular dentins. Methods This study investigated the antibacterial properties of 16 RMGI discs, containing 3 weight percent (wt.%) of silver and titanium nanoparticles prepared for each group. Also, the shear bond strength of RMGI discs containing nanoparticles between the coronal and radicular dentins were compared. Kolmogorov-Smirnov test was used to evaluate the normal distribution of data. Normally distributed data were analyzed and compared between the groups, using two-way ANOVA test; otherwise, Kruskal-Wallis test was performed to analyze the data. The level of statistical significance was set at 0.05. Results The mean colony count of S. mutans significantly reduced in both silver and titanium nanoparticle groups after 15 days compared to one-hour and 24-hour intervals (P<0.0001). The shear bond strength test revealed no significant differences between the two experimental groups (P>0.05). Conclusion Incorporation of silver and titanium oxide nanoparticles at a concentration of 3 wt.% yielded optimal antibacterial characteristics, without causing any significant changes in the shear bond strength. Comparison between nanoparticle containing RMGI and RMGI showed that over time it has more ability to create antibacterial properties against S. mutans bacteria.